Defective Glyoxalase 1 Contributes to Pathogenic Inflammation in Cystic Fibrosis - Marilena Pariano (MDPI AG, 2021)
Cystic fibrosis (CF) is an autosomal recessive disorder that affects multiple organs, although a decline in respiratory function represents the major cause of morbidity and mortality. The airways of CF patients are characterized by a chronic inflammatory state to which the receptor for advanced glycation end-products greatly contributes. Glyoxalase 1 (GLO1) is the major enzyme metabolizing methylglyoxal, a potent precursor of advanced glycation end-products. Its role in CF has never been investigated. We herein resorted to murine and human preclinical models of CF to define the contribution of GLO1 to inflammatory pathology. We found that the expression and activity of GLO1, measured by real-time PCR and Western blot or a specific spectrophotometric assay, respectively, are defective in mice and human bronchial cells from CF patients exposed to Aspergillus fumigatus, a common pathogen in CF, but could be restored upon blockade of interleukin-1 receptor signaling by anakinra in mice. This study suggests that GLO1 contributes to pathology in CF and may be potentially targeted to mitigate inflammation.